Evaluation of perceptions, knowledge and compliance with guidelines in real-life practice: A survey on the under-treatment of hypercholesterolemia - Volkan Doğan; Özcan Başaran; Bülent Özlek; Oğuzhan Çelik; Eda Özlek; Cem Çil; Ibrahim Halil Özdemir; Ibrahim Rencüzoğulları; Fatma Özpamuk Karadeniz; Lütfü Bekar; Mujdat Aktas; Mubariz Murat Resulzade; et al. (Türk Kardiyoloji Derneği Arşivi, 2019)
Objective: Few studies have directly assessed suboptimal management of dyslipidemia in Turkey. This study was conducted to assess patients' understanding and perceptions of high cholesterol as well as physicians' knowledge and awareness of lipid management strategies. Methods: This was a multicenter, observational study (ClinicalTrials.gov identifier: NCT02608645). Consecutive patients admitted to the participating cardiology clinics who were at least 18 years of age and who had been classified in a secondary prevention (SP) group or a high-risk primary prevention (PP) group were enrolled. The study population included 1868 patients from 40 sites in Turkey. Two-thirds (67.5%) of the patients in the SP group had been prescribed a statin, whereas only 30.1% of the PP group patients received statin therapy (p<0.001). Results: It was determined that 18% of the SP patients and 10.6% of the PP patients had a low-density lipoprotein cholesterol level at the recommended level (p<0.001). A patient survey revealed that almost half of the patients in the PP and in the SP groups were aware that their cholesterol levels were high. Negative information about statin treatment disseminated by media programs was the most common reason (9.4%) given for treatment discontinuation. Conclusion: Perceptions, knowledge and compliance with the guidelines for PP and SP patients in real-life practice have increased, but it remains far below the desired level. Patients and physicians should have more information about the treatment of hyperlipidemia. More accurate media programming could help to prevent the dissemination of misinformation.